Implementasi Sistem Informasi Pengembangan Kompetensi ASN Masa Depan (SI ABANG TAMPAN) pada Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kabupaten Bogor - Asropi, Asropi; Dimas Prabowo, Radityo; Dita Aryani, Nanda (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2024)
This study aims to analyze the implementation of the Future ASN Competency Development Information System (SIABANG TAMPAN) at the Bogor Regency Human Resources Development and Personnel Agency (BPKSDM). This research uses a descriptive method with a qualitative approach. Data collection was conducted by structured observation, documentation, literature study, and in-depth interviews. The conclusion of this study is that the implementation of the SIABANG TAMPAN application at the BKPSDM of Bogor Regency has gone well, but still needs improvement. The disposition factor has gone quite well, and has a positive influence on the application of SIABANG TAMPAN. Likewise, 3 other factors, namely communication, resources and bureaucratic structure contributed significantly to the successful implementation of SIABANG TAMPAN in Bogor Regency. However, there are several aspects that certainly need to be developed and improved in order to implement SIABANG TAMPAN. These aspects are the information clarity aspect which is a sub-factor of communication factors, the facility aspect in resource factors and the SOP aspect in bureaucratic structure factors.